TRANSYLVANIAN JOURNAL OF TOURISM AND TERRITORIAL DEVELOPMENT VOLUME 1 / ISSUE 2 / 2015 - DOMBAY, István; MAGYARI-SÁSKA, Zsolt; NIȚĂ, Adrian (2015)
The interest for the thematic routes began in the developed Western European countries, after 1970, when the “tourism explosion”, namely, the development of mass tourism, made it more specialized, but, also, better organized, in order to satisfy a diversified clientele. Different specialty studies pointed also the necessity to particularize the touristic offer for social groups with different preferences, which led to defining “thematic” attractions, such as: thematic parks, thematic events and thematic routes (Csapo, Berki, 2008). Concomitant with the growth of their importance for the tourism activities, the thematic routes were firstly justified locally, regionally and national wide, but also in international context.